2023
DOI: 10.1021/acsanm.3c00511
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Nanoparticles Electrodeposited on TiO2Nanotube Arrays Using Deep Eutectic Solvents for Implantable Electrochemical Sensors

Abstract: This work reports on the electrodeposition of zinc on nanoporous metal oxide titania nanotube arrays (TiO2 NTAs) using a zinc-containing deep eutectic solvent (Zn2+–DES). The effects of substrate morphology and crystallinity, deposition temperature, zinc concentration, and deposition time on the morphology and electrochemical properties of the Zn/TiO2 NTAs were investigated. Two-dimensional zinc nanohexagons (NHexs) with a mean diameter of ∼300 nm and a thickness of 10–20 nm were decorated onto the TiO2 NTAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Specifically, in the field of nanoscience and nanotechnology, DESs have been regarded as designer solvents. 15,16,27,28 DESs can be used to synthesize well-defined nanomaterials such as shape and size-controlled nanoparticles, 29–31 metal–organic frameworks, 32 electrodeposited films, 33,34 colloidal assemblies, 35 RNA/DNA architectures, 36,37 and hierarchically porous carbons. 27 DESs have been utilized as a suitable medium for the synthesis of functional and nanoscale materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in the field of nanoscience and nanotechnology, DESs have been regarded as designer solvents. 15,16,27,28 DESs can be used to synthesize well-defined nanomaterials such as shape and size-controlled nanoparticles, 29–31 metal–organic frameworks, 32 electrodeposited films, 33,34 colloidal assemblies, 35 RNA/DNA architectures, 36,37 and hierarchically porous carbons. 27 DESs have been utilized as a suitable medium for the synthesis of functional and nanoscale materials.…”
Section: Introductionmentioning
confidence: 99%
“…Cojocaru et al 33 utilized DESs to fabricate electrodeposited CoSm films. Wang et al 34 reported on the electrodeposition of zinc nanoparticles on titanium oxide nanotube arrays using DESs. Siegel et al 35 summarized the progress and prospects in synthesizing the colloidal nanoparticles and colloidal assemblies using DESs.…”
Section: Introductionmentioning
confidence: 99%
“…This nanocomposite already shows a good result in medical assessment process by reason of its higher surface volume proportion, less toxic, synthetic solidness, high isoelectric point, biocompatibility and proposed electron transfer is maximum. [24][25][26][27] An electrochemical sensor based on TiO 2 /ZrO 2 has been reported for the first time in this field.…”
mentioning
confidence: 99%